Study of Actor Networks and Discourse in the Policy of Formation of Land Bank in Indonesia - Hartanto, Lia Wahyu; Ningrum, Sinta; Setiawan, Tomi (Journal of Law, Politic and Humanities, 2025)
This study aims to determine the actor network and discourse that work in the context of land bank formation in Indonesia. This study uses a qualitative method with a network-based discourse analysis approach (Discourse Network Analysis) to understand the pattern of actor networks and policy discourse. Data were collected from online media coverage, academic studies, and related regulations. The results of the study found that the policy actor network consists of the Government, private sector, academics, media, and civil society groups with discourses that contest between investment interests and social justice. The implications of this study indicate that land bank policies accommodate the interests of investors more than the principle of social justice in agrarian reform. Therefore, a critical evaluation of the regulation and implementation of this policy is needed so as not to ignore people's rights to land